Single-arm study of camrelizumab plus apatinib for patients with advanced mucosal melanoma - Lin Li; Rong Huang; Huizi Sha; Baorui Liu; Zhengyun Zou; Guiying Zhang; Yu Ren; Fufeng Wang; Jiayu Wang; Lianjun Zhao; Kelin Zheng; Mengke Zhao; et al. (Journal for ImmunoTherapy of Cancer)
Background Previous studies have suggested the potential synergistic antitumor activity when combining immune checkpoint inhibitors with anti-angiogenic agents in various solid tumors. We aimed to assess the efficacy and safety of camrelizumab (a humanized programmed cell death-1 antibody) plus apatinib (a vascular endothelial growth factor receptor tyrosine kinase inhibitor) for patients with advanced mucosal melanoma (MM), and explore-related biomarkers.Methods We conducted a single-center, open-label, single-arm, phase II study. Patients with unresectable or recurrent/metastatic MM received camrelizumab and apatinib. The primary endpoint was the confirmed objective response rate (ORR).Results Between April 2019 and June 2022, 32 patients were enrolled, with 50.0% previously received systemic therapy. Among 28 patients with evaluable response, the confirmed ORR was 42.9%, the disease control rate was 82.1%, and the median progression-free survival (PFS) was 8.05 months. The confirmed ORR was 42.9% (6/14) in both treatment-naïve and previously treated patients. Notably, treatment-naïve patients had a median PFS of 11.89 months, and those with prior treatment had a median PFS of 6.47 months. Grade 3 treatment-related adverse events were transaminase elevation, rash, hyperbilirubinemia, proteinuria, hypertension, thrombocytopenia, hand-foot syndrome and diarrhea. No treatment-related deaths were observed. Higher tumor mutation burden (TMB), increased T-cell receptor (TCR) diversity, and altered receptor tyrosine kinase (RTK)/RAS pathway correlated with better tumor response.Conclusion Camrelizumab plus apatinib provided promising antitumor activity with acceptable toxicity in patients with advanced MM. TMB, TCR diversity and RTK/RAS pathway genes were identified as potential predictive biomarkers and warrant further validation.Trial registration number Chinese Clinical Trial Registry, ChiCTR1900023277.